Quantifying the Coding Playground: A Pilot Study Creating and Attempting to Validate a Rubric for Positive Technological Development - Levinson, Tess. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Marina Bers.; Committee: Richard Lerner, and Chris Rogers.; Keywords: Early childhood education, Science education, and Developmental psychology.